테니스화 착화 시 인지적 편안함과 관련된 운동역학적 변인 분석 - 곽창수; 전민주 (The Asian journal of kinesiology, 2014)
[목적] 본 연구는 단일 종목 판매량이 가장 높은 테니스화를 대상으로 착화 시 편안함과 관련된 운동역학적 요인을 규명하는데 그 목적이 있다. [방법] 본 연구의 피험자는 건강한 남자 대학테니스선수 10명이었다. 국내 시판되고 있는 대표적인 테니스화 5종을 대상으로 설문지를 이용하여 인지적 편안함과 관련된 착화테스트를 한 다음 가장 편한 신발과 가장 불편한 신발, 본인 신발의 3종류를 분석 대상으로 하였다. 4㎧의 속도로 달리기를 할 때 하지동작을 영상촬영과 지면반력측정, 압력분포측정을 통하여 각 분석변인들을 분석하였다. [결과] 아킬레스건각의 각변위(Δβpro )와 후족각의 각변위를 제외한 모든 후족제어 분석변인과 지면반력변인에서 통계적으로 유의한 차이를 나타내지 않았지만 편한 신발이 불편한 신발보다 크게 나타났다. 편안 신발은 불편한 신발에 비하여 전족부위(M1, M2, M3)와 후족부위(M6과 M7)의 부위별 평균 최대압력이 낮게 나타났다. M1, M3, M4, M6의 부위별 평균 최대압력은 편한 신발과 불편한 신발사이에 통계적인 차이를 나타났다(p<.05). 제1구간의 부위별 최대압력은 모든 부위에서, 그리고 제2구간에서 부위별 최대압력은 중족부위를 제외하고 통계적인 차이는 나타내지 않았으나 불편한 신발이 편한 신발에 비하여 더 크게 나타났다. [결론] 후족제어변인과 지면반력변인의 대부분은 편한 신발이 불편한 신발에 비하여 오히려 더 크게 나타났고, 압력분포변인은 불편한 신발이 편한 신발에 비하여 더 크게 나타났다. 이러한 결과는 인지적으로 편한 신발을 개발하는데 좋은 자료가 될 것으로 확신한다. 한편 본 연구결과 인지적으로 편한 신발이 불편한 신발에 비하여 크게 나타난 분석변인이 많은데 편한 신발과 상해발생 가능성에 대한 연구도 추후에 시도해 볼 만하다고 생각된다. [PURPOSE] The purpose of this study was to determine the factors related to cognitive comfort on tennis shoes which recorded the highest selling quantity of the single sports events. [METHOD] Subjects in this study were 10 male college tennis players with normal foot and no injuries in lower extremities. Five tennis shoe brands were used to test cognitive shoe comfort and the highest and lowest. Cinematography, force platform, and in-sole pressure distribution measurement system were used to analyze the lower extremity motion while running at the speed of 4m/sec. [RESULT] Rearfoot control variables and impact absorption variables were not shown statistically significant differences between comfort shoe and discomfort shoe. Torsion angle of discomfort shoes was significantly larger than comfort shoes(p<0.001). Regional average peak pressure of comfort shoes showed was shown to be larger than discomfort shoes in forefoot region and rearfoot region. Regional average peak pressure in M1, M3, M4, M6 was shown a statistically significant difference between comfort shoes and discomfort shoes(p<0.05). 1st phase and 2nd phase of the regional peak pressure were appeared to be larger in discomfort shoe than in comfort shoes. [CONCLUSION] It was suggested that increases in most of rearfoot control variables, impact force variables and pressure distribution variables may have been related to a decrease in perceived comfort. On the contrary, few findings of this study were decreases in comfort shoes. Therefore, future study for examining the relationship between comfort shoes and injury possibility should be followed. KCI Citation Count: 0